Effect of nutrient management on productivity and quality of malt barley cultivars in low temperature condition of Punjab - Kanwaljit Singh Sandhu; P. Kaur Gill (Annals of Agricultural Research, 2022)
The experiment was conducted at the students’ research farm of Khalsa College Amritsar, Punjab, India during rabi seasons of 2016-17 and 2017-18 to evaluate the performance of malt barley varieties in wheat dominating area of Punjab. The experiment was laid out in split plot design with three replications. Two varieties (DWRUB 52, DWRB 92) were kept in main plots and seven fertility levels (control, 80,100,120% recommended NPK, 80% NPK + 1%K foliar spray, 100% NPK + 1% K foliar spray, 120% NPK + 1% K foliar spray at grain filling stage) were kept in sub plots. Emergence time and count was almost similar in all treatments. Var. DWRB92 showed non-significantly higher plant height, leaf area, dry matter accumulation, effective tillers, ear length, kernel plumpness, protein content, grain and malt yield than DWRUB 52. On the other hand, var. DWERUB 52 produced significantly higher number of grains per spike than DWRB92. Application of NPK upto 120% recommended dose increased significantly the plant height (98.9 cm), leaf area (2.94), dry matter accumulation (111.2g), effective tillers (376), ear length (9.49 cm), number of grains per ear (28.59), 1000-grain weight (45.65g), grain protein content (10.4%), grain (4.63 t/ha) and malt yield (3.74 t/ha) over 80% recommended dose and control. Foliar application of K was proved beneficial for yield contributing and quality traits. Maximum net returns (`41108/ha) and B:C ratio (1.22) were obtained at 120% recommended NPK+1% K spray at grain filling stage.